2010
DOI: 10.4196/kjpp.2010.14.6.399
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Phasic and Tonic Inhibition in the Rat Visual Cortex

Abstract: Gamma-aminobutyric acid (GABA)-ergic inhibition is important in the function of the visual cortex.In a previous study, we reported a developmental increase in GABAA receptor-mediated inhibition in the rat visual cortex from 3 to 5 weeks of age. Because this developmental increase is crucial to the regulation of the induction of long-term synaptic plasticity, in the present study we investigated in detail the postnatal development of phasic and tonic inhibition. The amplitude of phasic inhibition evoked by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In accordance with the previous result, in the present study an increase of ∼20% in GABA A R‐mediated currents by diazepam was enough to suppress the induction of LTP at 5 weeks. We have also demonstrated that GABAergic inhibition continued to increase until 8 weeks of age (Jang et al, ) when plasticity was lower than at 5 weeks. Thus, an increase in the amplitude and the decay time constant of GABA A R‐mediated currents might be responsible for the developmental decrease in synaptic plasticity in the visual cortex.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In accordance with the previous result, in the present study an increase of ∼20% in GABA A R‐mediated currents by diazepam was enough to suppress the induction of LTP at 5 weeks. We have also demonstrated that GABAergic inhibition continued to increase until 8 weeks of age (Jang et al, ) when plasticity was lower than at 5 weeks. Thus, an increase in the amplitude and the decay time constant of GABA A R‐mediated currents might be responsible for the developmental decrease in synaptic plasticity in the visual cortex.…”
Section: Discussionsupporting
confidence: 54%
“…The changes in the subunit ratio shorten NMDAR currents (Carmignoto and Vicini, 1992) because NMDARs containing GluN2A subunits exhibit fast opening and closing kinetics (Paoletti, 2011). The subunit composition of GABA A Rs also appears to change during the critical period because the kinetics of GABA A R-mediated currents change at this period (Jang et al, 2010). It has been suggested that the changes in NMDAR and GABA A R interact to regulate synaptic plasticity (He et al, 2006;Philpot et al, 2007).…”
mentioning
confidence: 99%
“…In a previous study investigating the E-I ratio [ 15 ], we noticed that IPSPs increased with time when measured at 0 mV of membrane potential. In this study, we investigated the underlying mechanism for the increase in IPSP and elucidated the signaling pathways involved in the maintenance and regulation of phasic and tonic GABA A R-mediated inhibition.…”
Section: Resultsmentioning
confidence: 92%
“…Unlike the somatosensory cortex, in the visual cortex tonic GABA A -mediated currents increase with age (Jang et al, 2010). This may be related to the role of GABA in shaping neuronal circuits during a well-defined period of early postnatal development called critical period (Sale et al, 2010).…”
Section: Early In Postnatal Development Tonic Gabaergic Currents Difmentioning
confidence: 99%